Case Report: Effect of low energy availability and training load on sleep in a male combat sport athlete - Thomas, Craig; Langan-Evans, Carl; Germaine, Mark; Artukovic, Mario; Jones, Helen; Whitworth-Turner, Craig; Close, Graeme L.; Louis, Julien (Frontiers in Sports and Active Living, 2023)
Purpose: The aim of this case report was to describe the sleep responses in a male combat sport athlete, who was engaging in both chronic (CWL) and acute (AWL) weight loss practices in order to reduce body mass for a national competition. Methods: During the first seven weeks of training (Phases 1 and 2), the athlete adhered to a daily energy intake (EI) equating to their resting metabolic rate (1700 kcal·day-1) followed by a reduction in EI (1200-1300 kcal·day-1) in the 5 days before weighing in (Phase 3). Nocturnal sleep was monitored throughout the 8-week training period using wristwatch actigraphy and frequent measurements of body mass/composition, daily exercise energy expenditure and training load (TL) were taken. Results: The athlete was in a state of low energy availability (LEA) during the entire training period. There was a very large decrease in LEA status during phase 3 compared with phases 1 and 2 (3 v 20 kcal·kgFFM·day-1) and there was a small decrease in TL during phase 3 compared with phase 2 (410 v 523 AU). The athlete’s sleep efficiency increased throughout the training period, but total sleep time displayed a small to moderate decrease in phase 3 compared with phases 1 and 2 (386 v 429 and 430 min). However, correlational analysis demonstrated trivial to small, non-significant relationships between sleep characteristics and the athlete’s LEA status and TL. Conclusion: These findings suggest that CWL and AWL practices that cause fluctuations in LEA and TL may be implemented without compromising the sleep of combat sport athletes.